Lost boys, invisible girls: stories of Sudanese marriages across borders - Grabska, Katarzyna (Gender, Place & Culture, 2010)
Forced migration challenges and changes gender relations. The transnational activities of refugees resettled in the West create gender asymmetries among those who stay behind. This article explores the transnational marriages of young southern Sudanese women (‘invisible girls’), who either stayed in Sudan or remained in refugee camps in Kenya, to Sudanese men who were resettled to America, Canada or Australia (‘lost boys’). Incorporating gender as a relational category into the analysis of transnational practices that migrants and refugees engage in is important. The article argues that there is a need to put feminist analysis at the centre of transnational processes resulting from (forced) migration. It looks at the connections between different geographical locations, the impacts of the migration of young refugee men on bridewealth and marriage negotiations and the gender consequences for young women, men and their families. It is argued that transnational activities, such as marriage, contest, reconfigure and reinforce the culturally inscribed gender norms and practices in and across places. Transnational marriage results in ambiguous benefits for women (and men) in accessing greater freedoms. Anthropological analyses of marriage need a geographical focus on the transnational fields in which they occur. The article seeks to deepen understanding of the nuanced gendered consequences of transnationalism. It shows how gender analysis of actions taken across different locations can contribute to the theorisation of transnational studies of refugees and migrants.
Keywords: 2000 à aujourd'hui; 2000-2009; afrique; amériques; anthropologie; anthropologie sociale; approches et analyses; australie; canada; cours; discipline; histoire et politique; kenya; mariage; migration; océanie; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexisme; soudan; systèmes d'oppressions; thématiques; transnationalisme; états-unis

Les monologues voilés (Axe sud, 2010)
Véritable blockbuster, Les Monologues Voilés ont rencontré un succès phénoménal dès la création au Théâtre de Poche de Bruxelles. Depuis, le spectacle a été joué plus de 180 fois - à guichets fermés - en Belgique et à Paris.Le spectacle nous propose 12 monologues d'une exceptionnelle intensité, drôles, poétiques, émouvants nous offrant le rare privilège d'entrer dans l'intimité de femmes musulmanes, sans fausse pudibonderie ni voyeurisme. [source jaquette].
Place: Paris Publication Title: Scènes & Cies
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; approches et analyses; arabie saoudite; arts; asie; corps; cours; discipline; europe; féminisme islamique; irak; maroc; militance; pakistan; pays-bas; premier cycle; pédagogie; périodes historiques; régions géographiques; sex2283; somalie; thématiques; théâtre; turquie; égypte

Le genre d’une migration post-coloniale : de Meknès (Maroc) à Montréal (Québec) - Yolande Cohen (Genre & Histoire, 2010)
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; afrique; afrique du nord; amériques; approches et analyses; canada; cours; discipline; ethnographie; france; his4830; histoire; histoire du féminisme; histoire et politique; immigration; justice sociale; maghreb; maroc; migration; militance; mouvements des femmes*; mouvements féministes; point de vue situé; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques